2013
DOI: 10.1089/bio.2012.0059
|View full text |Cite
|
Sign up to set email alerts
|

“Proof of Concept” Pilot Study: Bioprocess Chain of Custody and Bioresource Sample Management Temperature Observations. Sample Level Temperature Trends and Stability Data Obtained Via Utilization of Bluechiip®Temperature Tracking Technology

Abstract: Temperature data collected heightened observations of sample temperature variability. Prevalence of bar-code label read failure and issues affecting reliability of barcode performance may be under-reported and unrecognized in sample management practice, particularly when the temperatures are lower than -60°C. It appears the bluechiip(®) tracking technology may offer increased reliability over one-dimensional (1D) bar-coding technology; however while promising these findings require validation in future trials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The National Cancer Institute (NCI), the International Society for Biological and Environmental Repositories (ISBER), and others have provided recommendations to ensure a more standardized approach for the collection, storage, and distribution of repository samples. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Many of these recommendations are based on studies examining the impact of specimen handling and processing on the overall quality of normal or solid tumor samples. 32,[39][40][41][42][43][44][45] Fewer studies have examined the impact of cryopreservation on the morphology, function, and molecular profiles of AML blasts, [46][47][48] although our group recently reported that delayed processing may adversely alter the leukemic transcriptome.…”
Section: Introductionmentioning
confidence: 99%
“…The National Cancer Institute (NCI), the International Society for Biological and Environmental Repositories (ISBER), and others have provided recommendations to ensure a more standardized approach for the collection, storage, and distribution of repository samples. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Many of these recommendations are based on studies examining the impact of specimen handling and processing on the overall quality of normal or solid tumor samples. 32,[39][40][41][42][43][44][45] Fewer studies have examined the impact of cryopreservation on the morphology, function, and molecular profiles of AML blasts, [46][47][48] although our group recently reported that delayed processing may adversely alter the leukemic transcriptome.…”
Section: Introductionmentioning
confidence: 99%
“…those being in development by Bluechiipt. 58 -The ideal biobank should offer an electronic sample inventory management system that eliminates paper-based tracking and reporting processes through all stages of a sample life cycle. Ideally, the system should have a reasonable level of interoperability with both internal and external collaborators, either through a common biospecimen inventory module as well as facile methods of exchanging and examining data.…”
Section: Inventory Management Workflow and Sample Tracking And Tempementioning
confidence: 99%